Application of the Five Domains model to food chain management of animal welfare: opportunities and constraints - Beausoleil, N. J.; Swanson, J. C.; McKeegan, D. E. F.; Croney, C. C. (Frontiers in Animal Science, 2023)
For businesses involved in animal production, ensuring high animal welfare standards has become the cornerstone of corporate social responsibility practices. Since animal welfare cannot be verified by consumers at the point of purchase, industry-led audits provide important assurance that animals used to produce food lived an acceptable quality of life and experienced a humane death. The Five Freedoms offer a simple tool to conceptualize the complex, multi-dimensional concept of animal welfare, and they have been widely adopted as a basic operational framework for compliance. However, the Five Freedoms are problematic in that they focus on the absence of negative welfare states, underemphasize the importance of positive experiences, are absolute, and represent a (mostly unattainable) ideal. The Five Domains model represents inter-related aspects of an animal’s welfare state, with four physical/functional domains used to infer likely mental experiences in the fifth domain. This model allows for consideration of both positive and negative affective experiences, recognizes degrees of welfare compromise, acknowledges that animals cannot be free from all negative experiences (and that indeed, some are essential for survival). Thus, the model better reflects current scientific understanding of animal welfare and – that ultimately, we are interested in how animals experience their lives. Nevertheless, caution is needed when inferring mental states, which can never be directly observed or measured, and hence the ultimate outcomes of the model’s application should be qualitative. Operationalization of the Five Domains offers several opportunities to improve the breadth and quality of welfare audits for production animals. The model can incorporate both resource/management- based and animal-based measures of welfare; the former reflect risks to animals’ welfare while the latter often provide direct information on the animal’s welfare state at the time of assessment. Existing welfare indicators may be linked to relevant mental states and evaluated accordingly, and new metrics may be scientifically identified. Importantly, the Five Domains structure demands scrutiny of the affective state consequences to animals of housing, handling, and husbandry procedures, and could improve the effectiveness of animal welfare training for auditors and stockpersons. Adoption of the Five Domains framework could facilitate improved communication about animal welfare in the food chain with customers and consumers.